Architecting the Euro. Issue 1 (18th March 2021) - Fabbrini, Sebastiano
Abstract : This article explores an obscure project in architectural history that a bank commissioned an interdisciplinary group of advisors to undertake in the mid-1990s. The task was to provide models to the participants in a design competition for the banknotes of a new currency — models that were not to be reproduced but only stylized, concealing any specific historical reference. After the winner was determined through an opinion poll, an unexpected by-product was the construction of actual buildings modeled after the stylized architectures on the banknotes. The distinctiveness of this process, and the reason for its complexity, lies in the fact that, contrary to what one may expect when discussing architecture and money (especially architecture on money), everything had to operate on a supranational level. The currency in question was the euro, which replaced the national currencies of twelve European states in 2002. The organization behind this endeavor was the European Monetary Institute, in collaboration with Gallup Europe. Its task force was asked to produce a historical survey of European architecture, whatever that might mean. As evidenced by the documents associated with this project, the primary requirement was to avoid national bias (EMI 1996: 2 ). As architecture and, more specifically, architectural history had been working in the opposite direction for centuries, this is a unique opportunity to explore how our discipline negotiated the process of nation-unbuilding and the emergence of a new, supranational structure of power in Europe.